Revision of the smaller-sized dorados (Salminus), with comments on the monophyly of the genus and its biogeography (Characiformes: Bryconidae) - Lima, Flávio C.t. (Zootaxa, 2022)
A revision of the genus Salminus, excluding the large-sized species S. brasiliensis and S. franciscanus, is presented. In addition to the two large-sized species, four additional Salminus species are recognized: Salminus affinis Steindachner, from the río Magdalena, río Sinú, and río Rancheria basins, Colombia; Salminus hilarii Valenciennes, from the rio Paraná, rio São Francisco, and rio Jaguaribe basins, Brazil, Argentina, and Paraguay; Salminus iquitensis (Nakashima), new combination, from the western portion of the Amazon basin, rio Branco, and río Orinoco basins, Bolivia, Brazil, Colombia, Ecuador, Peru, and Venezuela; and Salminus santosi new species, from the rio Tocantins basin, Brazil. These four species are described/redescribed and illustrated, and a key to the species belonging to the genus is presented. Comments on the diagnosis of the genus Salminus and its biogeography taking into account recent phylogenetic hypotheses published for the genus, are presented.